THE INFLUENCE OF INDIVIDUAL CHARACTERISTICS AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE AT PT. PERTA ARUN GAS LHOKSEUMAWE - Dea Amanda; Herman Fithra; Marbawi (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of individual characteristics and organizational culture on employee performance with organizational commitment as an intervening variable at PT. Perta Arun Gas Lhokseumawe, the dependent variables of this study are individual characteristics and organizational culture for the independent variable is employee performance, for the intervening variable is organizational commitment. The population in this study were employees at the Bener Meriah Regency Environmental Service totaling 182. The sampling technique used the census technique and obtained a sample of 182 respondents, there were 14 respondents who did not return the questionnaire so that the sample became 168 respondents who were employees at PT. Perta Arun Gas Lhokseumawe, the research method used was the quantitative method, for the data analysis method using Structural Equation Modeling (SEM). The results of this study indicate that individual characteristics and organizational culture have a significant effect on organizational commitment, then individual characteristics, organizational culture and organizational commitment have a significant effect on employee performance at PT. Perta Arun Gas Lhokseumawe. In this study, individual characteristics and organizational culture have a significant influence on employee performance through organizational commitment as an intervening variable. It can be concluded that organizational commitment functions as a full mediation between exogenous and endogenous variables.